THE IMPACT OF REGULATORY QUALITY ON DEEPENS LEVEL OF FINANCIAL INTEGRATION: EVIDENCE FROM THE EUROPEAN UNION COUNTRIES (NMS-10) - Ahmić, Azra; Isović , Ilma (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2023)
This study seeks to empirically explore whether the regulatory quality in the NMS-10 impacts deepening international financial integration and whether the strengthening of regulatory quality for NMS-10 has a causal effect on the level of international financial integration (IFI) in NMS-10. The study covers NMS-10 between 1995 and 2020. The estimation of parameters was made with descriptive statistics, the Breusch-Pagan test, the Pesaran test, the Granger causality test, and OLS regression to analyze the impact of REQ on IFI. The findings of the study reveal that regulatory quality has a statistically significant effect in deepening the process of financial integration for both periods, in the pre-accession and postaccession EU process. In addition, the results demonstrate that the regulatory quality of NMS-10 provides sound laws and policies that support the business environment, encourage cross-bordering financial transactions. Moreover, the results of the Granger causality test show that the level of global financial integration is causally impacted by the improvement in NMS-10 regulatory quality. This indicates that regulatory effectiveness might predicts international financial integration.